ON THE EFFECT ON THE ACOUSTIC PROPERTIES OF THE HUMEN TRACHEA AND MAIN BRONCHI OF BENDING VIBRATIONS OF CARTILAGES IN THEIR WALLS - Basovsky, V. G. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
Using the theory of bending oscillations of annular open rods, a calculation scheme for quantitative estimation of forced oscillations of tracheal and bronchial cartilages in the composition of the corresponding airways has been developed. It has been studied how the oscillations of these cartilages affect the acoustic properties of the human trachea and main bronchi. An improved acoustic model of the human trachea and main bronchi has been constructed, which allows to take more fully into account the relevant transfer functions to study the patterns of sound transmission from the main human airways to the outer surface of the chest.